Mineral status of soils and forages and effect of mineral supplementation on performance of lambs - Sendalo, D.S.C.; Mtenga, L.A.; Ekern, A. (1989)
A 148 days study was conducted at Morogoro to evaluate the mineral status of Blackhead Persian (BHP) lambs and their response to mineral supplementation under grazing conditions. Soil, forages and blood plasma were analysed monthly for Ca, Mg, P, K, Na, Cu, Fe and Zn. Also pH in soil and CP in forages were determined. Soil P, Cu and Zn, and forage CP, P, Na and Zn were in marginal levels to recommended requirements of lambs. Blood plasma P and Zn on the other hand were relatively high contrary to the low levels found in forages. Sex and mineral treatments did not have significant effect on blood plasm mineral composition. Mineral supplemented groups showed significant difference in final weight (P < 0.05), and daily gain (P < 0.01). Similarly, castrates were superior in final weight (P < 0.01) and daily gain (P < 0.01). There were no significant differences in carcass weight and composition due to treatments.